Demographic characteristics, risk factors and immunocytochemistry of p16INK4a, Ki-67, MCM5, and survivin as predictors for the progress of cervical precancer lesion (Medical Journal of Indonesia, 2010)
Aim To identify the predictive factors and biomarkers in the progression of cervical precancer lesion or CervicalÂ Intraepithelial Neoplasia (CIN). Methods The study was conducted from August 2007 to September 2008. Design of the study was case-control with stratifications of test dose response. The cases were patients with CIN. Control patients were non CIN patients. BivariateÂ analysis followed by multivariate analysis was conducted. Results There were 130 patients, consisting of 124 CIN patients divided into CIN 1, CIN 2 and CIN 3, with the following numbers of patients: 30, 41, and 33, respectively and 26 patients without CIN (non CIN). Bivariate analysis showedÂ that age < 41 years, education ≥13 years, sexual partner ≥2, first sexual relationship at age < 22 years, smoking, the presence of sexuallly transmitted infections, positive HPV DNA, high p16INK4a, Ki-67, MCM5 and Survivin expressionÂ constituted independent variables for the occurrence of CIN with P value of < 0.05. However, on multivariate analysis,Â independent variables that emerged were age, education ≥13 years, sexual partner ≥2 persons, positive HPV DNA, andÂ over expression of p16INK4a, Ki-67 and Survivin that showed a P value of < 0.005. Conclusion Younger ages, education age ≥13 years, sexual partner ≥2 persons, positive HPV DNA, high p16INK4a, Ki-67 and Survivin expression constituted the risk factors for the occurrence of the progress of CIN, and was used in theÂ equation to predict the progress of cervical precancer lesion. (Med J Indones 2010;19:147-53)